1995
DOI: 10.1007/bf00114505
|View full text |Cite
|
Sign up to set email alerts
|

Reversible vacuolation of the transverse tubules of frog skeletal muscle: a confocal fluorescence microscopy study

Abstract: A confocal microscope was used to investigate the reversible vacuolation of frog skeletal muscle fibres produced by the efflux and entry of glycerol (80-100 mM). The formation, development and disappearance of vacuoles was observed in the fibres by staining simultaneously with two fluorescent membrane probes, RH414 and DiOC6(3). The styryl dye, RH414, stains only the plasmalemma and the membranes of the transverse tubules. In normal and glycerol-loaded fibres, RH414 revealed regular, narrow dotted bands locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…The normal appearance of the sarcomeres can be appreciated in the DIC images of normal and mdx fibres after the enzymatic dissociation process. The di‐8 ANEPPS fluorescence images from both normal and mdx fibres showed a double row of T‐tubules per sarcomere, a distinctive feature of mammalian skeletal muscle fibres that has been documented previously (Revel, 1962; Dulhunty, 1989; Krolenko et al 1995; Franzini‐Armstrong et al 1998; Lannergren et al 1999). Importantly, there are no major T‐system structural differences between normal and mdx fibres.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The normal appearance of the sarcomeres can be appreciated in the DIC images of normal and mdx fibres after the enzymatic dissociation process. The di‐8 ANEPPS fluorescence images from both normal and mdx fibres showed a double row of T‐tubules per sarcomere, a distinctive feature of mammalian skeletal muscle fibres that has been documented previously (Revel, 1962; Dulhunty, 1989; Krolenko et al 1995; Franzini‐Armstrong et al 1998; Lannergren et al 1999). Importantly, there are no major T‐system structural differences between normal and mdx fibres.…”
Section: Discussionsupporting
confidence: 77%
“…In the magnified views in Fig. 1 and , it can be observed that the T‐tubules are organized in a double row per sarcomere pattern, a well‐known feature of mammalian skeletal muscle fibres that has been reported with electron microscopy (Franzini‐Armstrong et al 1988; Dulhunty, 1989) and with confocal fluorescence microscopy (Krolenko et al 1995; Lannergren et al 1999).…”
Section: Resultssupporting
confidence: 58%
“…The latter property underscores the role of the t-system in compartmentalizing its luminal solutes that would otherwise affect its excitability. The t-system is also a dynamic structure, changing its volume or vacuolating with osmotic stress or other factors (Krolenko et al, 1995;Krolenko and Lucy, 2001;Launikonis and Stephenson, 2002a;Launikonis and Stephenson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vacuoles in cells are formed by radiation injury, virustransformation and toxin injury [17][18][19]. Osmotic stress with glycerol also induces vacuolization of tubular system in muscle cells [20]. Vesicle membranes pass Cl -through ion channels [21,22], and Cl -is related to the regulation of water movements [23][24][25].…”
Section: Introductionmentioning
confidence: 99%